WACANA NARATIF KEHIDUPAN NABI ISA DALAM AL-QURʼAN - Edidarmo, Toto (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2014)
The Holy Quran contains the faith, worship, Islamic morals, history, promises and threats, and information about Hereafter (eschatology). The narrative style of the Quran is less systematic and intact except the narration of the Prophet Yusuf (Surah Yusuf [12]: 1-111). This paper narrates the verses of the Quran about Prophet Isa's life since his birth, prophetness, until death. The aim is to reconstruct narrative discourse of Prophet Isa's life as a systematical text. The method used is content analysis through verses related analysis in order to classify the meaning and connect the verses with other verses into a systematize form, a unified narrative and chronological discourse. DOI: 10.15408/a.v1i1.1133